2012
DOI: 10.5539/ijb.v4n2p102
|View full text |Cite
|
Sign up to set email alerts
|

Spawning and Nesting Behaviour of Tachypleus gigas along the East Coast of Peninsular Malaysia

Abstract: Present study was aimed to address the spawning and nesting behaviour of Malaysian horseshoe crab (Tachypleus gigas) in observed nesting grounds of East coast of Peninsular Malaysia during monsoonal period. Field sampling was carried out in every full and new moon days between September and December 2009 in Balok (Lat3°56.194' N, Long103°22.608' E) and Pekan (Lat3°36.181' N, Long103°23.946' E) nesting grounds. A total of 26 nests were found throughout the sampling period (Balok = 4 nests [~15%]; Pekan = 22 ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
1
15
1
1
Order By: Relevance
“…While acoustic transmitters were sensitive to wind and time consuming to locate crabs [26,27], manual tracking of spawning horseshoe crabs by observing the release of bubbles before and after spring tide is effective, feasible and low cost. Presently, the emergence of T. gigas to Balok was lower than previous records [15,18,20]. Past surveys at Tanjung Selangor, the only T. gigas spawning site with long term investigations in Malaysia showed that beach conditions during SW monsoon was most favourable to the horseshoe crab for spawning [21].…”
Section: Discussion Low Population Of Crabsmentioning
confidence: 64%
See 3 more Smart Citations
“…While acoustic transmitters were sensitive to wind and time consuming to locate crabs [26,27], manual tracking of spawning horseshoe crabs by observing the release of bubbles before and after spring tide is effective, feasible and low cost. Presently, the emergence of T. gigas to Balok was lower than previous records [15,18,20]. Past surveys at Tanjung Selangor, the only T. gigas spawning site with long term investigations in Malaysia showed that beach conditions during SW monsoon was most favourable to the horseshoe crab for spawning [21].…”
Section: Discussion Low Population Of Crabsmentioning
confidence: 64%
“…The arrival of three spawning amplexus at Cherating and another six at Balok is evident to small T. gigas populations in Malaysia [15,18,21] that consist of assemblages [31,32]. While dissimilar operational sex ratio (OSR) were observed in small population groups such as 1.07:1 at Maine [33] and up to 9:1 in larger groups [34], the absence of satellite male and solitary female produced OSR 1:1 at Balok and Cherating.…”
Section: Discussion Low Population Of Crabsmentioning
confidence: 99%
See 2 more Smart Citations
“…Balok (Lat3°56.194' N, Long103°22.608' E) in the Pahang state of East coast of Malaysia were observed to be the nesting ground of Horseshoe crabs Akbar John et al, 2011Zaleha et al, 2012). Adult horseshoe crabs migrate from the off shore continental shelf to spawn on intertidal sandy (T.gigas) and mud sandy beaches and mangrove area (C. rotundicauda) at every full and new moon at these sampling locations (Fig.…”
Section: Study Area Descriptionmentioning
confidence: 99%